2021
DOI: 10.1177/23197145211043799
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship in the Times of Pandemic: Barriers and Strategies

Abstract: Using a mixed method approach, this study investigates the challenges that the COVID-19 pandemic has posed for entrepreneurs and the strategies that organizations can adopt to make a turnaround towards survival and growth. Empirical analysis is done on the factors which have affected smaller firms during economic slowdowns in the past, and policies and plans adopted by firms to overcome the barriers. Factors such as lockdown, remote working, digital marketing and digitization were accounted through qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 54 publications
2
14
0
1
Order By: Relevance
“…In the strategic behavior of companies, the dynamic response capacity must prevail in the face of structural and conjunctural changes that have occurred. As was the case with the economic crisis that began in 2008, triggered after the bankruptcy of Lehman Brothers, the economic crisis caused by coronavirus disease 2019 (COVID-19) also represents a suitable natural experiment for the evaluation of economic resilience, corporate survival and the adequacy of the mechanisms of adjustment adopted by the companies (Chaturvedi and Karri, 2022). During the last decades, issues related to business resilience and management in times of systemic disruptions characterized by VUCA environments have emerged (Hamel and V€ alikangas, 2003;Linnenluecke, 2017;Lv et al, 2018;Somers, 2009;Williams et al, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In the strategic behavior of companies, the dynamic response capacity must prevail in the face of structural and conjunctural changes that have occurred. As was the case with the economic crisis that began in 2008, triggered after the bankruptcy of Lehman Brothers, the economic crisis caused by coronavirus disease 2019 (COVID-19) also represents a suitable natural experiment for the evaluation of economic resilience, corporate survival and the adequacy of the mechanisms of adjustment adopted by the companies (Chaturvedi and Karri, 2022). During the last decades, issues related to business resilience and management in times of systemic disruptions characterized by VUCA environments have emerged (Hamel and V€ alikangas, 2003;Linnenluecke, 2017;Lv et al, 2018;Somers, 2009;Williams et al, 2017).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…, 2015; Trahms et al. , 2013), with special emphasis on entrepreneurship (Chaturvedi and Karri, 2022; Latham, 2009; Robbins and Pearce, 1992) and innovation (Santana et al. , 2017; Hosseinzadeh Shahri and Nematollahi Sarvestani, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, small businesses face challenges in supplying new products to suit consumer demand in specific areas (Mehdi et al, 2021). Other challenges are vulnerable to environmental change, unregulated digital ecosystems, low fixed prices and less negotiating power among entrepreneurs (Chaturvedi & Karri, 2021;Karki & Risal, 2021;Mafimisebi & Ogunsade, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Related to this negative finding, Torr es et al (2022) found that entrepreneurs in France were at higher risk of burnout and bankruptcy during the pandemic. Also, Haltiwanger (2022) finds that small, entrepreneurial firms suffered disproportionately because of the pandemic (see also Chaturvedi and Karri, 2021 for a discussion of the effects of the pandemic on small businesses).…”
Section: Introductionmentioning
confidence: 99%